PERANCANGAN LEARNING MANGEMENT SYSTEM BERBASIS ANDROID - Muhammad Andi Firdaus; Ahmad Husain; Anggun Citra Dini Dwi Puspitasari (JURNAL ILMIAH INFORMATIKA, 2022)
The purpose of this research is to design a companion application for learning activities, previously SMPN 163 Jakarta used a third-party application to accompany learning activities. In addition, this study also aims to create an integrated and integrated learning companion application for SMPN 163 Jakarta to overcome the problem of inconsistency in the use of applications by each teacher at SMPN 163 Jakarta. The time of the study was carried out from March to July 2022. This study uses a qualitative approach by developing a system using research and development methods. The result of this research is the application that the researcher makes can integrate learning activities from third-party applications. With the application that the researcher made, the applications that are used as learning companions by the teachers of SMPN 163 Jakarta can be replaced with applications that the researchers made, and overcome the problem of inconsistency in the use of learning companion applications. In addition, with the application that the researcher made, it is possible to store administrative data for safer learning activities because they no longer use paper media so that there is no risk of paper being lost or torn.